Thermodynamic and thermophysical properties of combustion products (Jerusalem : Israel Program for Scientific Translations, 1974)
Vol.1. Computation methods -- v.2. Oxygen-based propellants -- v.3. Oxygen and air-based propellants -- v.4. Nitrogen tetroxide-based propellants